2014
DOI: 10.3892/ol.2014.2727
|View full text |Cite
|
Sign up to set email alerts
|

Role of antiviral therapy in reducing recurrence and improving survival in hepatitis B virus-associated hepatocellular carcinoma following curative resection (Review)

Abstract: Hepatocellular carcinoma (HCC) is one of the major causes of cancer-related mortality worldwide, with the majority of cases associated with persistent hepatitis B virus (HBV) or hepatitis C virus infection. In particular, chronic HBV infection is a predominant risk factor for the development of HCC in Asian and African populations. Hepatic resection, liver transplantion and radiofrequency ablation are increasingly used for the curative treatment of HCC, however, the survival rate of HCC patients who have under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…IFN-α also showed an antitumor effect by preventing angiogenesis, inhibiting tumor cell growth, inducing apoptosis of tumors, and increasing the immunogenicity of tumors [68,69]. The effect of IFN-α treatment in HBVrelated HCC patients can be both antiviral and anti-tumor [70]. IFN-α has been shown to prevent HCC development, but likely only in patients with cirrhosis.…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 95%
“…IFN-α also showed an antitumor effect by preventing angiogenesis, inhibiting tumor cell growth, inducing apoptosis of tumors, and increasing the immunogenicity of tumors [68,69]. The effect of IFN-α treatment in HBVrelated HCC patients can be both antiviral and anti-tumor [70]. IFN-α has been shown to prevent HCC development, but likely only in patients with cirrhosis.…”
Section: Antiviral Treatment Medicationsmentioning
confidence: 95%
“…It leads to deterioration of liver function, induces development of HCC and significantly affects prognosis of patients with HCC [124]. Zuo et al reported that viral reactivation was the most important correlative risk factor for HCC recurrence [125]. As sorafenib resistance becomes a hot topic, some researchers start to focus on the correlation between viral reactivation and sorafenib efficacy, with expectation to explore new treatment against HCC basing their potential correlation.…”
Section: Viral Reactivationmentioning
confidence: 99%
“…So far, the treatment for liver cancer is limited, the later stage or higher-grade liver cancer patients will ordinarily have poor prognosis [ 154 ]. Surgical resection may be the best therapy for promoting long-term survival, but because most patients are diagnosed at the later stage of disease, therefore only 10% of the patients are suitable for surgical resection.…”
Section: Recent Research On the Roles Of Herbs And Phytochemicals mentioning
confidence: 99%